2023
DOI: 10.1021/jacs.2c13566
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Roles of MA-Based Volatile Additives for α-FAPbI3 to Enable Efficient Inverted Perovskite Solar Cells

Abstract: Functional additives that can interact with the perovskite precursors to form the intermediate phase have been proven essential in obtaining uniform and stable α-FAPbI 3 films. Among them, Cl-based volatile additives are the most prevalent in the literature. However, their exact role is still unclear, especially in inverted perovskite solar cells (PSCs). In this work, we have systematically studied the functions of Cl-based volatile additives and MA-based additives in formamidinium lead iodide (FAPbI 3 )based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 50 publications
4
70
0
Order By: Relevance
“…Most of the works with certified PCE exceeding 25% have focused on the fine control of the perovskite crystallization process and surface defect passivation. [5,[25][26][27] This suggests that minimizing the non-radiative recombination loss in the bulk perovskite and at the charge-transporting layer (CTL)/perovskite interface is crucial for further closing the efficiency gap to reach the Shockley-Queisser (SQ) limit. [28,29] Colloidal SnO 2 has become the most used ETL in n-i-p PSCs (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the works with certified PCE exceeding 25% have focused on the fine control of the perovskite crystallization process and surface defect passivation. [5,[25][26][27] This suggests that minimizing the non-radiative recombination loss in the bulk perovskite and at the charge-transporting layer (CTL)/perovskite interface is crucial for further closing the efficiency gap to reach the Shockley-Queisser (SQ) limit. [28,29] Colloidal SnO 2 has become the most used ETL in n-i-p PSCs (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that MA can reduce the formation energy of the α-FAPbI 3 structure and Cl can enhance the interaction of FA and I, which is conducive to the stability of α-FAPbI 3 . 31,49 However, the kinetic and thermodynamic mechanisms of MA or Cl behavior are still unclear. In order to further clarify the respective roles of MA and Cl in the crystallization of α-FAPbI 3 films, IPA, MAI/IPA and FACl/IPA in the same molar ratio were chosen to replace MACl/IPA to fabricate perovskite films by the same CSA method at 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with 3C-FAPbI 3 of 1.409 eV, the band gap increases by about 0.013 eV, indicating that chloride ions mainly increase the band gap of 3C-FAPbI 3 single crystal caused by MACl additives. 24,36,49,50 Figure 7d presents the average results of multiple measurements: about 2% chlorine contributes to an increase of about 0.01 eV in the band gap. In comparison, 1% MFAI is associated with an increase of about 0.003 eV, whereas about 7% MA cations has almost no influence on the band gap.…”
Section: ■ Results and Discussionmentioning
confidence: 99%